IMPACT ON COMPUTATIONAL DIESEL SPRAY MODELS BY EVAPORATING AND NON-EVAPORATING CONDITIONS - Aftab Ahmed Soomro; Asmatullah; Safiullah; Basit Ahmad; Muhammad Nouman (Spectrum of Engineering Sciences, 2025)
This study explores the impact of diesel spray computation models and their constants by varying the parameters. Various enabled and disabled evaporating models based on changing the parameters i.e tip penetration, angle of inclination, evaporation ratios and spray shapes are compared with the experimental data to get their results. A viable automotive diesel injector was used in the experiments having nozzle diameter of 0.122mm. Sprays were injected with a pressure of 140 MPa. The measurements are taken of evaporating and non-evaporating spray in a high-pressure high-temperature constant volume vessel by adjusting ambient conditions. Simulation were taken of computational sprays using an Eulerian- Lagrangian two-phase fluid framework in a hexahedron cylindrical mesh box. The inputs including initial spray, rate of injection and angle of inclination were measured for the Computational Fluid Dynamics (CFD) simulation including with experimental methods. A systematic approach was used by enabling and disabling the various breakup models including primary, secondary and evaporation models for evaluation purpose. The results were demonstrated for secondary breakup models and their constants significantly influence the accuracy of spray predictions at non-evaporating conditions. While upon evaporation model the evaporating spray of droplet plays a crucial role in shaping the liquid penetration and evaporation ratios. This study provides intuitions into the importance of tuning model constants to achieve promising approach with experimental data, offering guidelines for improving diesel spray modeling in computational fluid dynamics (CFD) simulations.